(untitled) (Journal of Horizon, 2025)
The Primary Forest Moratorium Policy represents Indonesia’s most significant regulatory intervention intended to reduce deforestation, protect high-value carbon landscapes, and reinforce long-term climate mitigation commitments. This study analyzes the effectiveness of the moratorium, the legal loopholes that weaken its enforcement, and potential sustainability strategies to strengthen forest governance. Using a qualitative document analysis approach, the research synthesizes legal regulations, government publications, and peer-reviewed academic studies on forest policy and land governance in Indonesia. Findings indicate that the moratorium has successfully slowed permit-driven deforestation and improved environmental monitoring in high-risk areas, yet its implementation remains fragile due to overlapping sectoral regulations, ambiguous land classification rules, and economic dependency on extractive industries. These loopholes create institutional space for the continuation of forest exploitation through administrative rather than overt legal violations. The study concludes that long-term sustainability of the moratorium requires legal harmonization, standardized enforcement across governance levels, community land-rights protection, and economic transition policies that make conservation more advantageous than extraction. The article advances novelty by integrating effectiveness, legal loopholes, and sustainability into a single analytical framework to evaluate whether the moratorium can evolve from a symbolic pause into a durable climate governance instrument